Notary’s Legal Liability for Deeds Declared Null and Void - Almira Rahma, Ardita; Pujiyono, Pujiyono; Saptanti, Noor (CV. Inara, 2024)
Notary is a public official authorized to make authentic deeds. The authority of a Notary in making authentic deeds is the authority granted by the Notary Position Law as stipulated in Article 15 of Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 concerning Notary Position. Notarial deeds have perfect evidentiary power, which means that as long as no defects and untruths are found in the deed, the judge must be convinced and believe in the deed. However, if a dispute arises against the authentic deed, then the deed can be canceled or null and void. In carrying out his official duties towards an authentic deed he made, Notary is charged with a responsibility. So that if a deed is declared null and void, the Notary can be held accountable. This research is normative legal research, using library techniques and document studies to collect legal materials. analysis of legal materials in this study using deductive analysis. The results of this research show that, the form of Notary's responsibility for deeds declared null and void can include, civil responsibility, criminal responsibility and administrative responsibility.